Selenium-Enriched Fatty Goose Liver Attenuates Alcohol-Induced Liver Injury in Mice by Enhancing Antioxidant Capability - Bao-Wei Wang; Guo-Qing Huang; Wei-Wei Wang; Wen-Hua Ge; Ming-Ai Zhang (The Journal of Poultry Science, 2013)
The beneficial effects of dietary selenium (Se) supplementation for poultry and the distribution of Se in tissues have been well documented, but the functionalities of the Se-enriched products are much less concerned. Alcohol induces liver injury by initiating oxidative stress and antioxidant therapy has been proposed as an effective way of reducing the injury. Because a correlation between Se and antioxidant capability has been established, the alleviation effect of the Se-enriched fatty goose liver (SFGL, containing 900 μg/kg Se) on alcohol-induced liver injury was studied. Mice were daily fed with 2.5, 5, and 10 g/kg·bw SFGL and common fatty goose liver (CFGL, containing 200 μg/kg Se) one hour after ethanol administration and the animals were scarified and the blood and liver were collected for analysis on day 21. Results indicated that SFGL was more effective in reducing the hepatosomatic index and the degree of steatosis than CFGL. SFGL in all the three doses normalized the lipid metabolism and the activities of ALT and AST, indicating that SFGL attenuated the alcohol-induced liver injury. SFGL decreased the serum and hepatic ADH activities and the MDA content, implying that the liver injury attenuation effect of SGFL was related to oxidative stress reduction. The measurement of antioxidant variables, including GSH-Px, GSH, and SOD, revealed that the levels of these molecules were significantly increased after SFGL ingestion, confirming that SFGL alleviated alcohol-induced liver injury by enhancing the antioxidant capability. It was concluded that Se-enriched poultry tissues are potential remediators against alcohol-induced liver injury.